UP-Think in UDL Mathematics: Student Participation and Thinking Analysis - Panglipur, Indah Rahayu; Triyani, Septi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study evaluates the implementation of Universal Design for Learning (UDL) in mathematics instruction witha focus on students with visual impairments, a context that has not been sufficiently explored in higher education. Although UDL has been widely recognized as an inclusive approach, previous studies have primarily concentrated on general or primary–secondary education, leaving a gap in empirical evidence regarding its application in higher education mathematics. This research introduces the UP-Think (Understanding Participation and Thinking) framework as a novel contribution that integrates two essential dimensions: active student participation and higher-order thinking ability. Participation (asking, responding, collaborating); Thinking (conceptual, critical, creative) measured by easured by observation rubrics, a student-engagement questionnaire, pre–post concept-understanding tests, and a critical/creative thinking rubric with established reliability. Using a mixed-method descriptive evaluative design, data were collected from observations, questionnaires, pre–post tests, and interviews involving students of the Special Education Study Program. The results indicate a substantial increase in participation, with 79% (22/28) of visually impaired students more actively asking questions, 85% (26/28) responding and justifying answers, and 85% (26/28) engaging in group collaboration. In terms of thinking ability, 68% (19/28)achieved notable gains in conceptual understanding, 86% demonstrated consistent critical reasoning, and 78% displayed creative problem-solving strategies. These findings imply that accessible assessment design and lecturer training are essential for sustaining the benefits of UDL. Institutions should invest in systematic professional development and adaptive technology provision so that inclusive mathematics instruction can be implemented consistently and equitably across courses.